FATE AND EVENT KNOWLEDGE IN THE CREATIVITY OF ESHKABIL SHUKUR (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, the knowledge of fate and event in the poetry of Eshkabil Shukur is discussed in the poem "Three Wisdoms of Knowledge" in the series "Nasoyim ul-Muhabbat" poem "Sultanism Gadolik = science"; "man the afterlife = repentance"; "Wonder Soul Bird = Love"; "Two Worlds One Language = Truth" explored in artistic contrasts.